Spinal Epidural Cavernous Hemangiomas: A Clinical Series of 9 Cases and Literature Review - Zhao, Liyan; Jiang, Yining; Wang, Yubo; Bai, Yang; Sun, Ying; Li, Yunqian (Frontiers in Oncology, 2021)
Abstract Objective: Spinal epidural cavernous hemangiomas are very rare vascular lesions and are, therefore, seldom reported and easily misdiagnosed. Herein, we present a series of 9 cases with spinal epidural cavernous hemangiomas and discuss their pathogenesis, clinical characteristics, radiological findings, differential diagnosis, surgical interventions, pathological characteristics, and prognosis. Methods: We retrospectively retrieved and analyzed the data of patients with pure epidural cavernous hemangiomas, who underwent spinal magnetic resonance imaging, and surgical intervention at the First Hospital of Jilin University, China, between January 2005 and December 2019. The data on patients' clinical manifestations, imaging characteristics, surgical intervention, histopathological findings, and postoperative follow-up were also recorded and analyzed. Results: In all, 5 men and 4 women with the mean age of 61 years (range, 41–78 years) were recruited. All patients experienced a gradual onset of symptoms and a slowly progressive clinical course, and no patient presented an acute onset of symptoms. The clinical manifestations include myelopathic signs in 8 patients (88.9%) and radicular symptoms in 3 patients (33.3%). On T1-weighted imaging, 6 lesions appeared isointense (55.6%), and 4 lesions exhibited hypointense (44.4%) signals. On T2-weighted imaging, 8 lesions appeared hyperintense (88.9%), and 1 lesion was heterogeneously intense (11.1%). Following gadolinium administration, 5 lesions appeared homogeneous with significant enhancement (55.6%), 1 lesion was homogeneous and mild enhancement (11.1%), and 3 lesions were heterogeneous with mild enhancement (33.3%). All patients received early microsurgery assisted by intraoperative electrophysiologic monitoring and neuronavigation in the lateral position via the posterior midline approach. Five patients underwent total laminectomy (55.6%), and 4 underwent hemilaminectomy (44.4%). Total excision was achieved in all cases. The average follow-up period was 55.1 months (ranging 10–123 months). All patients exhibited significant clinical improvement of their neurological deficits and achieved a favorable outcome with no recorded recurrence at last follow-up. Conclusions: Spinal epidural cavernous hemangiomas are rare vascular malformations. Early surgical treatment with total resection is an optimum treatment, particularly for patients with an acute exacerbation onset. The prognosis is mostly good and depends predominantly on the severity of the preoperative status.